A Novel ARTP-derived Bacillus megaterium Mutant with Enhanced Salt Tolerance and Plant Growth Promotion in Saline–alkali Soil - Min Sun; PengFei Qiu; XinJie Yuan; QiLi Zhu; ZhenXing Peng; JiMin Lv; HongShun Li; JunPing Bao; YanQing Wei; ShuDong Qu; XianShun Ren; ZiHao Wang; et al. (Current Microbiology, 2026)
Soil salinization seriously threatens global food security with continuously expanding affected areas. Bacillus megaterium -based bioinoculant serves as an eco-friendly strategy for saline–alkali land remediation, whereas wild-type (WT) strains generally exhibit poor salt–alkali tolerance. To address this limitation, atmospheric and room temperature plasma (ARTP) mutagenesis combined with a microbial microdroplet culture (MMC) high-throughput screening system was adopted to screen high salt-tolerant B. megaterium mutant followed by multi-omics characterization. Using WT B. megaterium LD (CGMCC No.21828) as the original strain, a mutant library was constructed via optimized ARTP treatment, and the elite mutant SLD48 was isolated under dynamically increasing salt gradients. Compared with the wild type, SLD48 possesses a larger genome of 6,252,538 bp and acquires 28 extra functional genes including spoIVCA and pJ_gene0003 . Intracellular osmoprotectants (proline, glycine betaine) and antioxidant α-tocopherol were markedly accumulated in SLD48. moreover, exogenous supplementation of these substances in the culture medium can effectively alleviate the damage caused by salt stress to the cells. In pot trials with saline–alkali soil, the rhizosphere colonization of SLD48 reached 3.52 × 10⁵ CFU/g (2.46-fold of LD), and maize shoot fresh weight increased by 40.5% after inoculation. Collectively, this work confirms that mutant SLD48 is a promising microbial resource for saline–alkali soil improvement and crop yield promotion.